“Shang Chi And the Legend of The Ten Rings": Tense and Perspective - Rakhmyta, Yunie Amalia; Rusmiati, Rusmiati (English Learning Innovation, 2024)
Due to English's global significance, it indirectly affects Indonesia's education system. In this area of study, most scholarly publications speak English. All Indonesian nationals are required by law to take English classes. Many students have trouble understanding the grammatical rules of English because they are so different from those of their native language, Indonesian. The most important distinctions are those of tense and aspect. Many students struggle with grammar because of this. This analysis aims to determine which tenses and aspects are used in the script for "Shang Chi and the Legend of the Ten Rings," and which are employed most often. This research makes use of content analysis and qualitative descriptive methods. Data collection made use of record-keeping. The data was examined using the Miles and Huberman dynamic model. After the data has been compiled and presented, inferences can be made. The data shows that there are nine distinct permutations of tense and aspect. There are 33 current tenses, 37 past tenses, 6 future tenses, 35 progressive tenses, 3 past progressive tenses, 3 perfect tenses, 1 perfect tenses, 2 future perfect tenses, and 2 present perfect tenses. The present progressive is only represented by 35 occurrences, while the plain past tense is represented by 37. There are twelve permutations of tense and aspect, nine of which are used here. There is no distinction between past and future occurrences in the progressive tenses (future, past, and future perfect).